Model of Halal Tourism Management in Bukittinggi City, West Sumatra Province, Indonesia - Wibowo, Muhammad Ghafur; Khoiruddin, Akhmad Yusuf (International Journal of Publication and Social Studies, 2020)
The development of the halal tourism industry in Indonesia has increased in recent years. It is along with the support of the central government and also some local governments. Bukittinggi City in the Province of West Sumatra is a tourist city that has the potential to develop halal tourism. This study examines the model of managing Halal Tourism in the Bukittinggi City, West Sumatra Province, with the Penta Helix model that must involve various parties. The data was obtained from a questionnaire filled out by tourism policy stakeholders in the Bukittinggi City, which included business operators, local government officials, academics, religious leaders, and community leaders. The data is then processed by calculating the Priority matrix to produce alternative policies for the development of halal tourism. Collaboration between all components is very crucial. Policy priorities that must be selected and implemented by the Bukittinggi City government and all tourism people to develop halal tourism based on Analytical Hierarchy Process (AHP) and SWOT analysis are a collaboration with all tourism stakeholders, increase awareness of the importance of halal products, including in the field of tourism, and overcoming the limitations of halal restaurants and sharia hotels certified by Indonesian Ulama Council (MUI). This research contributes to the development of halal tourism in other areas to remain in accordance with Islamic values but also in harmony with local customs and culture.